Psychotic experiences and hyper-theory-of-mind in preadolescence – a birth cohort study. Issue 1 (8th September 2015) - Clemmensen, L.; van Os, J.; Drukker, M.; Munkholm, A.; Rimvall, M. K.; Væver, M.; Rask, C. U.; Bartels-Velthuis, A. A.; Skovgaard, A. M.; Jeppesen, P.
Abstract : Background: Knowledge on the risk mechanisms of psychotic experiences (PE) is still limited. The aim of this population-based study was to explore developmental markers of PE with a particular focus on the specificity of hyper-theory-of-mind (HyperToM) as correlate of PE as opposed to correlate of any mental disorder. Method: We assessed 1630 children from the Copenhagen Child Cohort 2000 regarding PE and HyperToM at the follow-up at 11–12 years. Mental disorders were diagnosed by clinical ratings based on standardized parent-, teacher- and self-reported psychopathology. Logistic regression analyses were performed to test the correlates of PE and HyperToM, and the specificity of correlates of PE v. correlates of any Diagnostic and Statistical Manual of Mental Disorders, 4th edition (DSM-IV) mental disorder. Results: Univariate analyses showed the following correlates of PE: familial psychiatric liability; parental mental illness during early child development; change in family composition; low family income; regulatory problems in infancy; onset of puberty; bullying; concurrent mental disorder; and HyperToM. When estimating the adjusted effects, only low family income, concurrent mental disorder, bullying and HyperToM remained significantly associated with PE. Further analyses of the specificity of these correlates with regard to outcome revealed that HyperToM was the only variable specifically associated with PE without concurrent mental disorder. Finally, HyperToM did not share any of the investigated precursors with PE. Conclusions: HyperToM may have a specific role in the risk trajectories of PE, being specifically associated with PE in preadolescent children, independently of other family and child risk factors associated with PE and overall psychopathology at this age.